Development and Evaluation of a Bilingual Banyumas Folklore-Based Interactive Audiobook for Early Childhood Language Skills - Ali, Musyafa; Prawening, Cesilia; Aji Jauhari Ma’mun, Ahmad; Aulia Nanda, Yuha; Wan Mokhtar, Wan Khairul Aiman (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2026)
Purpose – Bilingual, folklore-based digital learning media for early childhood remain scarce, and no prior study has empirically tested a bilingual (Javanese-Indonesian) interactive audiobook grounded in local folklore for its effect on early childhood language skills. This study addresses that gap by developing a bilingual, Banyumas folklore-based interactive audiobook and evaluating its effect on children's vocabulary, listening, and speaking skills.Design/methods/approach – This study followed a Research and Development (R&D) design adapted from the Borg and Gall model (Borg & Gall, 1983) and modified by Sugiyono, comprising needs analysis, product design, expert validation, revision, and effectiveness testing. Participants were 58 kindergarten children (two classes of 29) at a state kindergarten in East Purwokerto, assigned to experimental and control groups. A pretest–posttest non-randomized control-group design was used, and product effectiveness was analyzed statistically (normality, homogeneity, independent t-test, and N-Gain).Findings – The independent-samples t-test confirmed the experimental and control groups were statistically equivalent at pretest (Sig. 2-tailed = 0.372 > 0.05), ruling out a pre-existing advantage. After treatment, the experimental group achieved a mean N-Gain of 67.57% (medium-high,